Improving Photocatalytic Hydrogen Generation via Polycitric Acid-based Carbon Nanodots - Guldi, Dirk Michael; Langford, Daniel; Reva, Yana; Bo, Yifan; Gubanov, Kirill; Wu, Mingjian; Günay-Gürer, Ayşe; Mai, Lukas A.; Crisp, Ryan; Engelmann, Iryna; Spiecker, Erdmann; Fink, Rainer; et al. (Angewandte Chemie International Edition, 2025)
Bottom-up syntheses of carbon nanodots (CND) using solvothermal treatment of citric acid are known to afford nanometer-sized, amorphous polycitric acid-based materials. The addition of suitable co-reactants in the form of in situ synthesized N-hetero-π-conjugated chromophores facilitates hereby the overall functionalization. Reports regarding the influence of CND on the properties of, for example, N-hetero-π-conjugated chromophores are scarce. Thus, our incentive was to design a CND model that features phenazine (P-CND) – a well-known N-hetero-π-conjugated chromophore – to investigate the influence of the CND matrix on its redox chemistry as well as photochemistry. The scope of our work was to go beyond investigating the electrochemical properties of the resulting P-CND by shedding light onto differences relative to nano-aggregates of phenazine (PNZNA), which served as reference. In particular, chemical as well as electrochemical reduction of PNZNA initiated a reaction cascade that affords the primary reduction intermediate, that is, the reduced and protonated (PNZ-H)⋅. In accordance with existing literature, the final product of a bimolecular disproportionation was 5,10-dihydrophenazine (PNZ-H2). Reducing P-CND also resulted in the formation of (PNZ-H)⋅. But, no evidence for a subsequent bimolecular disproportionation was gathered. Instead, (PNZ-H)⋅ as an integrative part of P-CND was found to be actively involved in a H2 generation reaction. A more than twofold increase in efficiency compared to PNZNA under identical conditions was the consequence.
CRIS-Team Scopus Importer:2025-02-28
Keywords: carbon nanodot; phenazine; pulse radiolysis; reduction; transient absorption